METHODOLOGY FOR DEVELOPING SPEED-STRENGTH QUALITIES OF SCHOOLCHILDREN THROUGH ATHLETICS - Sh.D.Djahongirov (Research Focus International Scientific Journal, 2025)
this article explores a methodology for developing speed-strength qualities in schoolchildren through athletics. The study highlights the importance of incorporating athletic activities into physical education programs, presenting an experimental approach to improve students' physical capabilities. Results indicate significant improvements in speed and strength metrics, suggesting practical applications for educators and coaches.